THE IMPACT OF INTERIOR DESIGN ELEMENTS ON VISITOR ATTRACTION AT CIHAPIT MARKET’S WET MARKET ZONE - Putri Nabilah Tsana; Santi Salayanti; Agustinus Nur Arief Hapsoro (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Traditional markets play a vital role in Indonesia’s economic and socio-cultural landscape but continue to face challenges related to comfort and spatial appeal. This study aims to analyze the influence of interior elements on visitor perception in the wet market area of Cihapit Market, Bandung, with particular attention to gender-based differences through the lens of multisensory theory. A mixed-method approach was employed, combining field observations grounded in Environmental Behavior Studies (EBS) with questionnaires involving 100 respondents. The findings reveal that male visitors tend to be more critical of functional aspects, particularly spatial circulation, which is perceived as ineffective due to narrow pathways and faded floor markings. In contrast, female visitors are more sensitive to multisensory aspects, such as dim lighting, low cleanliness caused by stagnant water and organic waste, and poor air quality due to pervasive fishy odors. These results highlight that spatial experience in traditional markets is shaped by complex multisensory interactions in which visual, tactile, kinesthetic, and olfactory stimuli collectively influence perceptions of comfort and safety. Therefore, interior design strategies for traditional markets should focus on integrating inclusive multisensory experiences to enhance comfort, attractiveness, and competitiveness amid changing modern consumer behaviors.